Penanganan stunting melalui peningkatan pengetahuan dan sikap masyarakat terhadap sanitasi lingkungan - Abu, Nur; Yasin, Azalia Fajri; Ayuningtias, Annisa (Holistik Jurnal Kesehatan, 2024)
Background: National stunting prevalence fell by 3.3% from 27.7% in 2019 to 24.4% in 2021. However, the reduction in stunting in the Papua and West Papua regions increased from 2019 to 2021 by 29.4%. Based on the Indonesian Nutrition Status Survey (SSGI), the city of Sorong experienced an increase of 27.2% from 2021-2022. Purpose: To know of the influence of knowledge, attitudes and environmental sanitation on the incidence of stunting. Method: Quantitative design research, the sample was randomly selected from the local community as many as 85 respondents. The variables in this research are knowledge, attitudes and environmental sanitation. Bivariate analysis uses the chi-square test to see the influence and relationship between knowledge, attitudes and environmental sanitation. Results: A p-value of 0.005 indicates a relationship between attitudes towards stunting and environmental sanitation. The p-value of 0.190 shows that there is no dominant relationship between knowledge of stunting and environmental sanitation. Furthermore, the p-value of 0.027 shows that there is a relationship between knowledge and attitudes towards stunting. Conclusion: Knowledge and attitudes have a dominant influence on the incidence of stunting compared to environmental sanitation.   Keywords: Attitude; Knowledge; Sanitation; Stunting.   Pendahuluan: Prevalensi stunting secara nasional turun sebanyak 3.3% dari 27.7% tahun 2019 menjadi 24.4%  pada tahun 2021. Namun penurunan stunting di wilayah Papua dan Papua Barat mengalami peningkatan dari tahun 2019 sampai 2021 sebesar 29.4%. Berdasarkan Survei Status Gizi Indonesia (SSGI), kota Sorong mengalami peningkatan sebesar 27.2% dari tahun 2021-2022. Tujuan: Untuk mengetahui pengaruh pengetahuan, sikap, dan sanitasi lingkungan terhadap kejadian stunting. Metode: Desain penelitian kuantitatif, sampel dipilih secara acak kepada masyarakat setempat sebanyak 85 responden. Variabel pada penelitian ini adalah pengetahuan, sikap, dan sanitasi lingkungan. Analisis bivariat menggunakan uji chi-square untuk melihat pengaruh dan hubungan antara pengetahuan, sikap, dan sanitasi lingkungan. Hasil: P-value sebesar 0.005 menunjukkan adanya hubungan antara sikap terhadap stunting dan sanitasi lingkungan. Hasil p-value sebesar 0.190 menunjukkan tidak ada hubungan yang dominan antara pengetahuan terhadap stunting dan sanitasi lingkungan. Selanjutnya hasil p-value sebesar 0.027 menunjukkan ada hubungan antara pengetahuan dan sikap terhadap stunting. Simpulan: Pengetahuan dan sikap mempunyai pengaruh yang dominan terhadap kejadian stunting dibandingkan dengan sanitasi lingkungan.   Kata Kunci: Pengetahuan; Sanitasi; Sikap; Stunting.